The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1177/002029401304600203
|View full text |Cite
|
Sign up to set email alerts
|

Developing Measurement Facilities for Carbon Capture and Storage

Abstract: This paper describes two experimental facilities developed to carry out research and development of measurement instruments used in the Carbon Capture and Storage (CCS) industry. The gaseous and static facilities are capable of testing measurement devices such as flowmeters, densitometers and sampling systems. Testing these instruments in the compositions and conditions likely to be experienced in the industry is essential to ensure that they are capable of achieving the required levels of uncertainty specifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The existing NEL wet gas facility was developed for gaseous CO 2 flow measurement, and orifice plates, Coriolis meter and ultrasonic flowmeters were tested. They concluded that at some of existing metering technologies could be within the CCS uncertainty requirements …”
Section: Challenges Of Metering Technologies For Ccsmentioning
confidence: 99%
See 3 more Smart Citations
“…The existing NEL wet gas facility was developed for gaseous CO 2 flow measurement, and orifice plates, Coriolis meter and ultrasonic flowmeters were tested. They concluded that at some of existing metering technologies could be within the CCS uncertainty requirements …”
Section: Challenges Of Metering Technologies For Ccsmentioning
confidence: 99%
“…It seems clear that there is no current single metering system which can, on its own, fulfil all of the requirements for metering CO 2 in CCS. It is apparent that some technologies, such as orifice plate meters, which are well proven in other applications (generally the least complex and best understood types of meters) are unsuitable for CCS due to uncertainties around EoS . This is further complicated by, in some instances, significant changes in the physical condition of the fluid caused by the measurement device itself.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This generally involves the transportation of CO2 gas from the capture sites to storage locations such as saline formations and depleted oil and gas reservoirs [1]. CCU differs from CCS in the final destination of the captured CO2 in which it is instead converted into commercial products rather than transferred to a suitable site for long-term storage [2].…”
Section: Introductionmentioning
confidence: 99%